Biomimetic Metal-Organic Framework Nanoparticles for Synergistic Combining of SDT-Chemotherapy Induce Pyroptosis in Gastric Cancer - Yu, Zhu; Cao, Wenlong; Han, Chuangye; Wang, Zhen; Qiu, Yue; Wang, Jiancheng; Wei, Mengda; Wang, Junfu; Zhang, Siwen; Liu, Senfeng; Mo, Shutian; Chen, Junqiang (Frontiers in Bioengineering and Biotechnology, 2022)
In recent years, sonodynamic therapy (SDT) has been widely developed for cancer research as a promising non-invasive therapeutic strategy. Here, we synthesized Zeolitic imidazole frameworks-8 (ZIF-8) and utilized its properties to encapsulate hydrophobic Chlorin e6 (Ce6) and hydrophilic tirapazamine (TPZ) for a synergistic sonodynamic-chemotherapy, which was also accompanied by the modification of cytomembrane of gastric cancer (GC) cells. Thus, we enabled the biomimetic property to achieve targeted delivery. Ce6-mediated SDT, in combination with ultrasound irradiation, could target the release of reactive oxygen species (ROS) to aggravate further hypoxia and activate TPZ. Combining these effects could induce the pyroptosis of GC cells and play the anti-tumor function, which could provide a potential therapeutic method for cancer therapy.